Selective Phosphodiesterase 1 Inhibitor BTTQ Reduces Blood Pressure in Spontaneously Hypertensive and Dahl Salt Sensitive Rats: Role of Peripheral Vasodilation - Dey, Asim B.; Khedr, Sherif; Bean, James; Porras, Leah L.; Meredith, Tamika D.; Willard, Francis S.; Hass, Joseph V.; Zhou, Xin; Terashvili, Maia; Jesudason, Cynthia D.; Ruley, Kevin M.; Wiley, Michael R.; et al. (Frontiers in Physiology, 2020)
Regulation of the peripheral vascular resistance via modulating the vessel diameter has been considered as a main determinant of the arterial blood pressure. Phosphodiesterase enzymes (PDE1-11) hydrolyse cyclic nucleotides, which are key players controlling the vessel diameter and thus peripheral resistance. Here, we have tested and reported the effects of a novel selective PDE1 inhibitor (BTTQ) on the cardiovascular system. Normal Sprague Dawley, spontaneously hypertensive (SHR), and Dahl salt sensitive rats were used to test in vivo efficacy of the compound. Phosphodiesterase radiometric enzyme assay revealed that BTTQ inhibited all three isoforms of PDE1 in nanomolar concentration, while micromolar concentrations were needed to induce effective inhibition for other PDEs. The myography study revealed a potent vasodilatory effect of the drug, which was confirmed in vivo by an increase in the blood flow in the rat ear arteriole reflected by the rise in the temperature. Furthermore, BTTQ proved a high efficacy in lowering the blood pressure in all studied rat models. Moreover, additional blood pressure lowering could be achieved when BTTQ was administered on top of ACE inhibitor lisinopril, a current standard of care in treatment of hypertension. Therefore, PDE1 inhibition induced an efficient vasodilation that was accompanied by a significant reduction of blood pressure in different hypertensive rat models. Administration of BTTQ was also associated with increased heart rate in both model of hypertension as well as in the normotensive rats. Thus, PDE1 appears to be an attractive therapeutic target for treatment of resistant hypertension.